Revisions to international accounting standards : IAS 16, Property, plant and equipment, IAS 28, Accounting for investments in associates, IAS 31, Financial reporting of interests in joint ventures - International Accounting Standards Committee (London, U.K. : International Accounting Standards Committee., 1998)
Contains
International accounting standard, IAS 16 (rev. 1998); International accounting standard, IAS 28 (rev. 1998); International accounting standard, IAS 31 (rev. 1998).
"September 1998."
Supersedes: IAS 16 (approved 1993); paragraphs 23 and 24 of IAS 28 (approved 1994); paragraphs 39 and 40 of IAS 31 (approved 1994) with a new paragraph 41 inserted.
oif 30/03/15
Loan
Keywords: Factories -- Accounting -- Standards; Industrial equipment -- Accounting -- Standards; Joint ventures -- Accounting -- Standards; Financial statements -- Standards; Investments -- Accounting -- Standards